Pelatihan dan Bimbingan Permainan Bola Voli untuk Remaja di Usia Produktif - Sony Ardiantama; Zakwan Ahmad (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this activity is to provide training and guidance in playing volleyball for teenagers of productive age. The method used is a demonstration which consists of two stages. In stage I, the team provided material that was carried out during service activities, such as passing, smash, serve and block techniques. Stage II is direct practice of the material that has been delivered until completion while the service team carries out the activities. In phase II, the team did it in stages over several weeks. The team carries out training three times a week so that what the team provides can be quickly understood by them so they can be more enthusiastic and healthier. On the first day when providing training, the teenagers were enthusiastic about doing the exercises, but they got tired easily because it was the first time doing the activity, but their enthusiasm and enthusiasm was enough to make the team happy because many people took part in the training. The team was divided into two fields, one field for teenage boys and another field for teenage girls. The youth leader helps the team provide training. The youth leader helps provide training to teenage girls, and the service implementation team provides training to teenage boys. The service activities were carried out well as indicated by the teenagers being very enthusiastic, because their parents paid attention to them while the team was carrying out training activities. The results achieved are that through this service activity we can provide solutions to the problems experienced by partners. In this case, the people in Padamulya Village, Majalaya District, Bandung Regency are starting to open themselves up to participate in afternoon activities in the form of gymnastics carried out at the village office. This activity is very beneficial for health and immunity. This activity opens up people's mindset about the importance of maintaining health. Knowledge about health increases and can be applied towards a healthy society, and is an activity that has succeeded in encouraging people's interest in maintaining health, both their own health in particular and the Padamulya Village community in general.